Variation in sunscreen compounds (mycosporine‐like amino acids) for marine species along a gradient of ultraviolet radiation transmission within doubtful sound, New Zealand - Miles D. Lamare; Michael P. Lesser; Mike F. Barker; Thomas M. Barry; Kate B. Schimanski (New Zealand Journal of Marine and Freshwater Research, 2004)
We examined the response of four species of New Zealand marine algae ( Ecklonia radiata, Apophlaea lyallii, Rhodymenia spp., Ulva lactuca ) and a sea urchin ( Evechinus chloroticus ) to spatial variation in ultraviolet radiation (UV‐R) by examining the concentration of UV‐R absorbing compounds known as mycosporine‐like amino acids (MAAs). The purpose was to understand how, and the degree to which, local marine species could potentially respond to any future increases in incident UV‐R in the New Zealand marine environment. The research was undertaken in Doubtful Sound, where we observed a gradient of water column UV‐R transmission along the 40 km length of the fiord. We examined spatial differences in MAAs along the UV‐B gradient in the macrophytes and temporal changes in MAAs in sea urchin gonads. Among the algae, thallus MAA concentrations (nmol mg –1 protein) ranged from 12.5 to 87.8 in E. radiata , from 433.1 to 1446.4 in A. lyallii , 12.7 to 103.4 in Rhodymenia spp., but were not detected in U. lactuca . For E. chloroticus , gonadal MAA concentrations ranged from 83.9 to 224.3 nmol mg –1 protein spatially, and over the year from 1.85 to 14.12 nmol mg –1 dry weight (DW) depending on site and gametogenic cycle. Laboratory manipulations indicated that concentrations of MAAs in E. chloroticus gonads and eggs are influenced by diet. MAA concentration could be correlated with UV‐B intensities in two of the algal species. E. chloroticus MAA concentrations could also be correlated with UV‐B transmission, which we concluded was a reflection of the greater ingestion and accumulation of MAA‐rich macrophytes at those sites where higher ambient UV‐R induced greater MAA concentrations to occur in the algae. Given this, we suggest that one response of marine species to increases in UV‐B would be an increase in the synthesis and/or accumulation of MAAs for photoautotrophs and a dietary accumulation of those MAAs in E. chloroticus , an important herbivore in this system.

Transmission of ultraviolet radiation through the Antarctic annual sea ice and its biological effects on sea urchin embryos - Michael P. Lesser; Miles D. Lamare; Michael F. Barker (Limnology and Oceanography, 2004)
Stratospheric ozone depletion over Antarctica is expected to continue for the next 50 years, with increases in ecologically damaging ultraviolet radiation (UVR: 290–400 nm), specifically the ultraviolet‐B (UVB: 290–320 nm) portion of the spectrum. Most of coastal Antarctica is covered with 2–3 m of annual sea ice during the occurrence of the “ozone hole.” This physical barrier to UVR transmission has long been assumed to provide complete protection from the biologically damaging effects of UVR, especially for the planktonic developmental stages of the benthic invertebrate fauna. We found that short‐wavelength UVB (down to 304 nm) is transmitted through the Austral spring annual ice of McMurdo Sound, and causes significant mortality and DNA damage in the embryos of the sea urchin Sterechinus neumayeri . Although mortality of sea urchin embryos has been reported for the open waters of the Antarctic, this is the first documentation of mortality and DNA damage for embryos under the annual sea ice. The degree of mortality and DNA damage was dependent on both year and depth, with higher mortality and DNA damage at 1 m depth below the ice compared to 3 m and 5 m. Greater DNA damage occurred in 2003 compared to 2002 despite the thicker annual ice (3.1 m vs. 2.5 m). Although the thickness of the annual ice was greater, the severity of the ozone hole, 230 Dobson units (DU) versus 320 DU, and the ratio of UVB to visible radiation was greater in 2003. Embryo and larval mortality from exposure to UVR under the annual ice should be considered as another abiotic factor potentially affecting the temporally episodic recruitment of invertebrates that occur in this benthic ecosystem.

Exposure to solar radiation increases damage to both host tissues and algal symbionts of corals during thermal stress - Michael P. Lesser; Julianne H. Farrell (Coral Reefs, 2004)